The Effect of Yoga on Blood Pressure Clogging For Hypertension Sufferers Patients - Bangun Wijonarko; Viyan Septiyana Ahmad (Jurnal teknologi Kesehatan Borneo, 2022)
Hypertension is a silent killer where this disease often attacks without any signs and symptoms that appear. The prevalence rate is very large in the world, this disease is the number one disease in the world. Objective: to determine the effect of yoga exercise on reducing blood pressure in hypertensive patients in the Neglasari Community Health Center, Tangerang City. The method used in this study is a quasi-experimental method. Method: The research design used was one group pretest-posttest design. The research sample was taken by propursive sampling with 16 respondents. Results: From the results of the average difference test, the 1st and 2nd measurements show a value of 0.000. While the 1st diastole is 0.003 and the 2nd diastole is 0.000. Conclusion: the results of measuring the mean difference in systole 1, systole 2, diastole 1 and diastole 2 show the results of p <0.005; it can be concluded that there is an effect of reducing blood pressure before and after doing yoga exercises.